The impact of antithrombotic therapy in patients undergoing emergency laparoscopic cholecystectomy for acute cholecystitis ‐ A single center experience. Issue 3 (20th August 2019) - Imamura, Hajime; Minami, Shigeki; Isagawa, Yuriko; Morita, Michi; Hirabaru, Masataka; Kawahara, Daisuke; Tokai, Hirotaka; Noda, Kazumasa; Inoue, Keiji; Haraguchi, Masashi; Eguchi, Susumu
Abstract: Aim: The risk of developing hemorrhagic complications during or after surgery in patients receiving antithrombotic therapy remains uncertain. Moreover, the impact of antithrombotic therapy under an acute inflammatory status is unclear. We investigated the impact of antithrombotic therapy in patients undergoing emergency laparoscopic cholecystectomy for acute cholecystitis. Methods: This record‐based retrospective study included patients who underwent emergency laparoscopic cholecystectomy for acute cholecystitis between September 2015 and January 2019. Patients who received elective laparoscopic cholecystectomy, open cholecystectomy, or gallbladder drainage before surgery were excluded. We evaluated the diseases for which antithrombotic therapy was administered, background characteristics, laboratory parameters and perioperative outcomes of patients with acute cholecystitis. The primary outcomes were intraoperative bleeding, blood transfusion requirement, conversion to an open procedure, and postoperative complications, including bleeding. Results: One hundred and twenty‐one patients (non‐antithrombotic therapy, n = 92; antithrombotic therapy, n = 29) were analyzed. There were differences in age and American Association of Anesthesiologists class ( P < .05), but not in the grade of acute cholecystitis ( P = .19). There were no differences in the operation time (non‐antithrombotic vs antithrombotic therapy: 142 [58‐313] vs 146 minutes [65‐373], P = .85), bleeding (17.5 mL [1‐1400] vs 25 mL [1‐1337], P = .58), blood transfusion requirement (n = 3 [3.2%] vs n = 2 [6.9%], P = .59) and the number of cases converted to open surgery (n = 8 [9%] vs n = 2 [7%], P = 1). The rates of postoperative complications, including bleeding, did not differ between the two groups and there was no mortality in either group. Conclusion: Emergency laparoscopic cholecystectomy could be planned for patients receiving single antithrombotic therapy, similar to patients who were not receiving antithrombotic therapy.